STRATEGI ADAPTASI MASYARAKAT DI DESA PANTAI BAHAGIA, MUARA GEMBONG, BEKASI TERHADAP DAMPAK BANJIR ROB - Ferry Dwi Cahyadi; Mad Rudi; Rizky Erliana Andari (Universitas Pattimura, 2022)
Pantai Bahagia Village in Muara Gembong District, Bekasi Regency is the most affected village so far from tidal flooding, and some of its areas have been permanently inundated by sea water. The purpose of this study is to describe the impact of tidal flooding and how the community adapts in Pantai Bahagia Village in dealing with tidal flooding. Data collection methods used include observation and interviews which are then analyzed descriptively qualitatively. The results obtained are that it is known that the tidal flood that occurred caused Muara Flag Village, Gobah Village, Muara Pecah Village, Beting Village, and Muara Mati to be inundated by sea water. The height of inundation from tidal flooding ranges from 20 cm - 70 cm. Adaptations made by the community include raising the foundation of the house, installing a water pump in the house.